The higher learning in America : a memorandum on the conduct of universities by business men - Veblen, Thorstein, 1857-1929 (Johns Hopkins University Press, 2015)
"Veblen's insights into the American university system at the outset of the twentieth century are as provocative today as they were when first published. Insisting that institutions of higher learning should be dedicated solely to the disinterested pursuit of knowledge, he urged American universities to abandon commitments to extraneous pursuits such as athletics, community service, and vocational education. He also believed that the corporate model of governance--with university boards of trustees dominated by well-to-do businessmen and university presidents who functioned essentially as businessmen in academic dress--mandated unsavory techniques of salesmanship and self-promotion that threatened to reduce institutions of higher learning to the status of competitive business enterprises."--Publisher's Web site